Muksa Dalam Pamuksa - YB Rahno Triyogo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
Pamuksa is Lakon which tells that heaven and hell are choices. Heaven is togetherness with the divine, the source of life, while hell is the separation of humans from the divine which is synonymous with eternal suffering, which is also known as eternal death. The purpose of this paper is to solve problems related to moral values contained in the wayang lakon Pamuksa. This article takes a moral approach. Based on this approach, the result shows that, firstly, humans will get happiness if they prioritize heavenly values in their lives. Secondly, the filial piety of children towards parents has great power or power in saving parents from eternal suffering.